New Pandemic, Old Walls - Cinkevich, Mark (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Mark Cinkevich Title (English): New Pandemic, Old Walls Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 142-142 Page Count: 2 Citation (English): Mark Cinkevich, “New Pandemic, Old Walls,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 142-143.